Biophysical approach to low back pain: a pilot report. (June 2015) - Foletti, Alberto; Pokorný, Jiry
Abstract Since biophysical treatment has been reported to be effective in the general management of pain, we decided to assess the specific effect and treatment duration of this therapeutic strategy in low back pain. We were interested in verifying the possibility that a single clinical procedure could reduce pain and improve patients' quality of life within a period of three months. An Electromagnetic Information Transfer Through Aqueous System was employed to record endogenous therapeutic signals from each individual using an electromagnetic recording device (Med Select 729). A highly significant reduction in the Roland Morris low back pain and disability questionnaire score was observed after 3 months following a single biophysical intervention (11.83 ± 6 at baseline versus 2.3 ± 3.25 at 3 months, p < 0.0001). This preliminary report provides further evidence of the theoretical implications and clinical applications of Quantum Electro Dynamic concepts in biology and medicine.